Effect of pH of Suspension and Mechanical Treatment on Nanosized Zirconia Dispersion / Noor Faeizah Amat...[et al.] - Amat, Noor Faeizah; Muchtar, Andanastuti; Ghazali, Mariyam Jameelah; Yahaya, Norziha (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Understanding zirconia 3YSZ powder dispersion is crucial in achieving colloidal stability in order to produce high-strength and translucent structures required for dental applications. In this work, pH adjustment (pH 1–11) and mechanical treatment (ball milling, ultrasonic treatment, and centrifugation) were employed to remove agglomeration. As-received zirconia 3YSZ powder was characterized by transmission electron microscopy, Brunauer–Emmett–Teller method, and laser light scattering technique to identify the primary particle size and to verify the presence of powder agglomeration. Particle dispersion of nanosized zirconia 3YSZ in aqueous suspension at various pH and different mechanical treatments were investigated by measuring the particle size distribution and zeta potential. The particle size of zirconia powder after adjustment to pH 2 was found to decrease (195 nm) compared with that of the as-received powder (388 nm), thus indicating the occurrence of powder de-agglomeration. A higher zeta potential value was also observed at pH 2. The isoelectric point of the suspension was at pH 10.7, where agglomeration was found to occur. This result is in good agreement with the average particle size result, in which larger particle sizes were observed at pH 10 to 11. In addition, ball milling was found to be an effective method to remove weak agglomeration given that small particle sizes measuring 164 nm were produced, whereas ultrasonic and centrifugation treatments worsened the powder dispersion. Zirconia suspension at pH 2 and prepared via ball milling was well-dispersed and suitable for further consolidation process.